Nusantara Tajwid Literature in Colonial Era Studi on Methodological Characteristics and Discourse of Anti-Colonialism in Naẓam Taḥsīnah by KH. Ahmad Rifa’i (1786-1875) - Kamelia, Ning Dian; Faizah, Fatikhatul (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2022)
This article discussed tajwid Naẓam Taḥsīnah by KH. Ahmad Rifa'i, one of the oldest recitation books in the archipelago, in addition to the position of KH. Ahmad Rifa'i is a scholar who pioneered the use of the pegon script in his writing on the one hand and as a colonial resistance movement on the other. This study used a socio-historical approach to see the context and explore the thoughts of KH. Ahmad Rifa'i in the book Naẓam Taḥsīnah and the context that surrounds it in the background of Dutch colonialism in the 19th century AD. Several stages are passed in the form of inventorying data, selecting and classifying it, then reconstructing and conducting a critical analysis of the basic assumptions. The results of these findings are; First, the background of Dutch colonialism which took place in the 19th century AD directly shaped the thinking of KH. Ahmad Rifa'i when writing Naẓam Taḥsīnah to carry out non-physical resistance with anti-colonial narratives inserted in his book. Second, the Naẓam Taḥsīnah has its own characteristics in composing the discussion of tajwid science, that using naẓam in Javanese pegon and containing anti-colonial narratives which conveyed through terms, such as pious scholars, pious scholars, infidels, and hypocrites. Those terms were aimed at the attitude of Dutch anti-colonialism as well as a form of non-physical resistance and secretive, but able to embrace students and the community.